MALDI-TOF-MS for rapid screening analysis of M-protein in serum - Li, Jie; Xu, Anping; Xie, Weijie; Li, Bowen; Yan, Cunliang; Xia, Yong; Liang, Chao; Ji, Ling (Frontiers in Oncology, 2022)
Monoclonal immunoglobin (M-protein) is a serum biomarker for the diagnosis of plasma cell dyscrasias. Despite limitation of analytical sensitivity and resolution, serum protein electrophoresis and immunofixation electrophoresis are still the front-line tests for the detection of M-proteins. Herein, we developed a MALDI-TOF Mass spectrometry-based method for the screening test of M-proteins in human serum. Based on the unique mass signature of different immunoglobin isotypes, M-Proteins could be rapidly identified and typed. The method demonstrated with high analytical performance and throughput, rapid and simple, which could be a new choice for the diagnosis of plasma cell dyscrasias.